Answer:
The correct option is: A. [tex]\frac{x^1^2}{64}[/tex]
Step-by-step explanation:
Given expression is: [tex](4x^-^4)^-^3[/tex]
First we will apply the outer exponent -3 with both 4 and [tex]x^-^4[/tex] inside the parenthesis. So, we will get: [tex](4)^-^3(x^-^4)^-^3[/tex]
Now, [tex](4)^-^3 = \frac{1}{(4)^3}= \frac{1}{64}[/tex]
and [tex](x^-^4)^-^3= x^(^-^4^)^(^-^3^) = x^1^2[/tex]
Thus, [tex](4)^-^3(x^-^4)^-^3 = (x^1^2)(\frac{1}{64})= \frac{x^1^2}{64}[/tex]
So, the simplified answer is [tex]\frac{x^1^2}{64}[/tex]